(3GdSdWI GdQFGSjI (B/s - (3MSf eMeO YhGVIs; (3KQhJ HOhjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1976)
(3JfbSe gPg GdQSGdI Edi bSejf; MjK jJfGhd GdbSe GdChd GdSdWI GdQFGSjI, hGdbSe GdKGfj jJfGhd JWhQ GdSdWI GdQFGSjI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1976.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI UaMGJ (B281 - 290.s
Keywords: (3GdbGfhf GdOSJhQjs; (3GdSdWI GdQFGSjIs; (3GdhXjaI GdQFGSjIs; (3GdQFjS GdEOGQjs; (3ZUH GdSdWI s; (3GdehXa GdaYdjs; (3CLgRI GdJCOjHs; (3eHOC GdbjGOI GdEOGQjIs; (3fbGHGJ GdehXajfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs